Highly Sensitive Immunoassay for the Diagnosis of Acute Myocardial Infarction Using Silica Spheres Encapsulating a Quantum Dot Layer - Han, Hyojeong; Pyun, Jae-Chul; Yoo, Hyein; Seo, Hong Seog; Jung, Byung Hwa; Yoo, Young Sook; Woo, Kyoungja; Kang, Min-Jung (AMER CHEMICAL SOC, 2014)
Commercial ELISA kits for substance P (SubP), which are helpful for the clinical diagnosis of acute myocardial infarction, are limited in efficacy because of low sensitivity. A highly sensitive immunoassay was developed using silica spheres encapsulating a quantum dot-layer (SQS) and labeling antibodies, on a Parylene A-modified plate. The high sensitivity was possible by taking advantage of the enhanced photoluminescence of the SQS and dense immobilization of SubP on a Parylene A-modified plate. Glutaraldehyde was used for cross-linking of SQS to the anti-SubP antibody and SubP to the Parylene A coating. The SQS-linked immunosorbent assay (SQSLISA) was optimized and validated. The dynamic range for the assay was 1-10000 pg/mL with a linear correlation factor of 0.9992 when the competitive SQSLISA was employed. The intra- and interday accuracies were 93-100% and 87-122%, respectively. The reproducibility was lower than 11%. The developed method was applied to clinical samples collected from healthy controls (n = 30) and acute myocardial infarction (n = 16) and it displayed a high correlation with the commercial ELISA kit, with a limit of detection that was 30-fold lower. Clinical sample analysis confirmed that SubP is a promising diagnostic marker for acute myocardial infarction. The SQSLISA is expected to be a practical and useful assay tool.
Keywords: CARDIAC TROPONIN-I; SUBSTANCE-P; PROGNOSTIC VALUE; MYOGLOBIN; PROTEIN; ASSAY; QUANTIFICATION; ANTIBODIES; MORTALITY; RECEPTOR